The Use of Guess the Word Game in Learning English Vocabularies - Yuliana; Antoni, Rivi (Journal of Applied Linguistics, 2024)
This study aimed to examine the effectiveness of the use of the “Guess the Word" game in learning English vocabulary at public elementary school 25 Tambusai. Using a classroom action research design, the study involved 10 fourth-grade students who participated in two learning cycles over four weeks. Data was collected through pre-tests and post-tests, class observations, as well as students’ interviews. The research analysis results in a better improvement in students, vocabulary mastery and pronunciation skills. The majority of students achieved better progress; five students in the range of 55-75 and four students in g a high score in the area of 75-85. In addition, the use of the word game in learning activities also develops students’ confidence and active participation in comprehending new vocabulary. In short, this study concludes that the game "Guess the Word" was an effective strategy for improving vocabulary mastery and developing a fun learning activity. Keywords : Game; guess the Word;Vocabularies